The Current Landscape of Access to Electrical Energy - Trujillo-Rodríguez , César Leonardo (Ingeniería, 2024)
Universal access to affordable, reliable, sustainable, and modern energy is one of the Sustainable Development Goals (SDGs7) set for 2023. Although the number of people with access to electricity was close to 91% as of 2021, it is concerning that, according to the energy progress report elaborated by the World Bank and the UN in 2023, 765 million people around the world lack this service.